Proof of the Mysterious Efficacy of Ginseng: Basic and Clinical Trials: Effects of Red Ginseng on Learning and Memory Deficits in an Animal Model of Amnesia - Hisao Nishijo; Teruko Uwano; Yong-Mei Zhong; Taketoshi Ono (Elsevier, 2004)
Ameliorating effects of red ginseng on learning and memory deficits due to hippocampal lesions and aging were reviewed; the performance of young rats with selective hippocampal lesions with or without red ginseng (p.o.), and aged rats with or without red ginseng (p.o.) in the spatial learning tasks was compared with that of sham-operated or intact young rats. Each rat was tested with 3 types of spatial learning tasks (distance movement task, DMT; random reward place search task, RRPST; and place learning task, PLT) in a circular open field using intracranial self-stimulation (ICSS) as reward. The results in the DMT and RRPST indicated that motivational and motor activity of young rats with hippocampal lesions with and without ginseng and aged rats with and without ginseng were not significantly different from that of control young rats. However, young rats with hippocampal lesions without ginseng and aged rats without ginseng displayed significant deficits in the PLT. Treatment with red ginseng significantly ameliorated place-navigation deficits in young rats with hippocampal lesions in the PLT. Similarly, red ginseng improved performance of aged rats in the PLT. The results, along with previous studies showing significant effects of red ginseng on the central nervous system, suggest that red ginseng ameliorates learning and memory deficits through effects on the central nervous system, partly through effects on the hippocampal formation. However, its mechanisms are still unclear, and further studies are required. Keywords:: Panax ginseng, aging, memory deficit, hippocampus, ischemia